2022
DOI: 10.31548/ujvs.13(1).2022.44-51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Biosapin Probiotic and the Biolide Disinfectant on the Microclimate of Poultry Houses

Abstract: Currently, in the field of poultry farming, the issue of using disinfectants for surface treatment of poultry houses, incubators and hatching eggs is particularly acute. Preparations must be both effective for the destruction of pathogenic microorganisms resistant to antibacterial substances, and safe for the environment, productive poultry and poultry goods. The purpose of this study was to test the Biosapin probiotic and the Biolide disinfectant in industrial conditions of a poultry house and incubator room.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Modern disinfectants should ensure the proper state of veterinary and sanitary welfare and reliable protection against infections, thus, they are one of the elements in the prevention of infectious diseases of productive animals and poultry in the technological process of their cultivation. Thus, previous studies by the authors (Chechet et al, 2021;Chechet et al, 2022;Kovalenko et al, 2022) and several other scientists (Melnyk, 2017;Demchyshyn et al, 2018) in in vitro and in vivo experiments have established the effectiveness and safety of biocides based on organic acids, peroxide compounds, chlorine dioxide, etc. As described by J.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Modern disinfectants should ensure the proper state of veterinary and sanitary welfare and reliable protection against infections, thus, they are one of the elements in the prevention of infectious diseases of productive animals and poultry in the technological process of their cultivation. Thus, previous studies by the authors (Chechet et al, 2021;Chechet et al, 2022;Kovalenko et al, 2022) and several other scientists (Melnyk, 2017;Demchyshyn et al, 2018) in in vitro and in vivo experiments have established the effectiveness and safety of biocides based on organic acids, peroxide compounds, chlorine dioxide, etc. As described by J.…”
Section: Introductionmentioning
confidence: 96%
“…Chechet et al (2022) and V.L. Kovalenko et al (2022) have demonstrated that the disinfectants "Diolaid" and "Biolaid" have an active antimicrobial effect against gram-positive and gram-negative bacteria, fungicidal properties, virulent effect and prevent resistance of microorganisms to the drug. V.L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation